Primary lymphoma of bone in a 60-year-old diabetic patient: a case report (BIRDEM Medical Journal, 2025)
In this report, we discuss an atypical case of bone pain caused by primary lymphoma of bone. A 60-year-old, diabetic, normotensive male presented with constant, unremitting pain in different bones. X-ray showed lytic lesion and fine needle aspiration cytology from the bone revealed non-Hodgkin lymphoma. Due low prevalence, primary bone lymphoma is often diagnosed late.BIRDEM Med J 2025; 15(1): 47-50